Effects of Directed Attention on Subsequent Processing of Emotions: Increased Attention to Unpleasant Pictures Occurs in the Late Positive Potential - Chen, Yuming; Zhang, Dandan; Jiang, Donghong (Frontiers in Psychology, 2018)
Directed attention is a fundamental mental resource for voluntarily managing the focus and direction of cognitive resources. The present study investigated how processing of unpleasant and neutral images is affected by emotion and previous directed attention. The results showed that there was enhanced early posterior negativity, anterior N2, and parietal late positive potential (LPP) in response to unpleasant pictures compared to neutral pictures. Furthermore, attention history (i.e., whether stimuli were previously attended to) modulated the amplitudes of the anterior N2 and parietal LPP. Most notably, an interaction between attention history and emotion was found in the LPP: pictures with an ‘attended history’ evoked larger LPP amplitudes than pictures with an ‘unattended history’, but this effect was only significant for unpleasant pictures (not for neutral pictures). These results suggest that directed attention to affective pictures facilitates subsequent neural processing of these pictures, and that this effect was amplified by unpleasant emotions experienced in the LPP. The current findings provide further empirical evidence of a two-stage model of emotion-attention interaction.